Groundwater Risk Assessment as an Impact of Land Use in the Groundwater Basin of Salatiga, Province of Central Java, Salatiga - Kesuma, Destha A.; Purwanto, Purwanto; Putranto, Thomas T.; Rahmani, Tara Puri Ducha; Santi, Sintha Soraya (Future Science)
Variation of land use can affect the quality of groundwater and increase the potential for groundwater contamination. Physical environmental conditions that have a low sensitivity to contamination of groundwater, but the use of land which could potentially generate pollutants, such as industrial areas, residential, the agricultural activity can increase the risk level of contamination in the groundwater in the area. The purpose of this study is to develop a groundwater risk to contamination map in the shallow aquifer and to determine priority areas of groundwater quality monitoring in Salatiga Groundwater Basin. Groundwater risk to contamination map was prepared on aspects of land use and the degree of vulnerability of groundwater to contamination using DRASTIC methods and spatially was prepared by using Geographic Information System. Results of the assessment of risk levels obtained worth the risk index 93-204. The risk index values are grouped into five (5) classes of risk: low, low to medium, medium, medium-high, and high. The output of this research can be input for local governments in understanding the possible spread of groundwater contamination as well as choosing the right strategy for the conservation of groundwater resources in the Groundwater Basin of Salatiga.